SAT0226 A phase 1, randomized, double-blind, placebo-controlled, single- and multiple-rising dose study of the btk inhibitor tak-020 in healthy volunteers. (12th June 2018) - Esfandiari, E.; Gevorkyan, H.; Faessel, H.; Zhao, Z.; Hanna, K.; Smithson, G.; Wagner, J.; Fedyk, E. R.; Mclean, L.
Abstract : Background: TAK-020 is a highly selective covalent inhibitor of the Btk enzyme. Btk is involved both in B cell receptor and FcR signaling. TAK-020 showed anti-inflammatory and disease-modifying efficacy in a rat collagen-induced arthritis model and is in clinical development, with potential for immune disorders including RA and SLE. Objectives: To assess the safety, tolerability, pharmacokinetic (PK) and pharmacodynamic (PD) properties of TAK-020. Methods: The study population comprised healthy volunteers aged 18 to 55 years. The SRD had 9 cohorts and the MRD 6, each randomized 6 active- to 2 placebo-treated subjects. 72 subjects were enrolled in the SRD, with 6 each receiving 0.1 mg, 0.5 mg, 2.5 mg, 4.4 mg, 8.8 mg, 17.5 mg, 35 mg, 70 mg, or 105 mg of TAK-020; and 18 subjects received placebo. 48 subjects were in the MRD, six each receiving 7 once-daily (OD) doses of 3.75 mg, 5.75 mg, 13 mg, 25 mg, 45 mg, or 60 mg. A total of 30 subjects received placebo. The PD effects of TAK-020 were assessed by measuring Btk occupancy and the inhibition of FcεR1-mediated activation of basophils, a Btk-dependent process resulting in increased CD63 expression. Results: In the SRD the same percentage of subjects (11.1%) in the pooled placebo group and the overall TAK-020 group experienced treatment-emergent adverse events (TEAE). All TEAEs were of mild intensity. Abdominal distension, upper abdominal pain, nausea, and headache were reported as drug-related TEAEs in 3 subjects in the TAK-020 group. In the MRD a lower percentage of subjects receiving TAK-020 had TEAEs than with placebo (30.6 vs 41.7%). In 4 subjects (11.1%) these were considered drug-related and included nausea, diarrhea, dizziness and headache. There were no serious AEs or AEs leading to study drug discontinuation. No subject had clinically significant changes in laboratory tests, vital signs, or ECGs. TAK-020 was rapidly absorbed (median Tmax 45- 60 min), and had a mean elimination half-life of approximately 3- 9 hr after single and multiple dosing. Plasma exposure was in general proportional to dose up to 70 mg administered as a single dose and up to 60 mg after 7d of OD dosing. Single doses of TAK-020 were associated with rapid binding of Btk, with occupancy >80% and maintained for 72 hours. Sustained binding of Btk was associated with >80% reduction from baseline in the proportion of CD63-positive basophils. This PD effect was sustained throughout the entire 24 hr dosing interval after administration of the 2 highest repeat doses of TAK-020 (45 and 60 mg) but fully reversed 1 week after the last dose. Conclusions: TAK-020 was well tolerated in healthy volunteers after single and multiple doses, and demonstrated target engagement and biological activity. The PD effects outlasted PK exposures, as expected for a covalent inhibitor. Disclosure of Interest: E. Esfandiari Shareholder of: Takeda, Employee of: Takeda, H. Gevorkyan Employee of: Parexel, H. Faessel Shareholder of: Takeda, Employee of: Takeda, Z. Zhao Shareholder of: Takeda, Employee of: Takeda, K. Hanna Employee of: PRA, G. Smithson Shareholder of: Takeda, Employee of: Takeda, J. Wagner Shareholder of: Takeda, Employee of: Takeda, E. Fedyk Shareholder of: Takeda, Employee of: Takeda, L. Mclean Shareholder of: Takeda, Employee of: Takeda